Hubungan Karakteristik dengan Tingkat Kepatuhan Penggunaan Obat pada Diabetisi Tipe 2 Prolanis di Wilayah Kerja Puskesmas Wonopringgo Kabupaten Pekalongan - Nuniek Nizmah Fajriyah; Wulan Agustin Ningrum; Ainun Muthoharoh; Tia Listiana (Prosiding University Research Colloquium, 2019)
Diabetes mellitus is characterized as a disease or chronic metabolic disorder with multiple etiologies, including disruption to pancreatic beta cells, reduced insulin secretion, and excessive sugar consumption.This study intends to determine the association between the attributes and the level of drug-like using compliance in individuals with type 2 diabetes Prolanis in the Wonopringgo Puskesmas Work Area, Pekalongan Regency. This research is a non-experimental observational study. A total of 50 patients were evaluated using univariate and bivariate assessment with the inclusion requirements of patients diagnosed with Prolanis type 2 diabetes at the Wonopringgo Public Health Center in Pekalongan District, willing to engage in the research, and DM patients with or without corresponding diseases. The characteristics and compliance of drug use can be seen on the basis of filling out the questionnaire with the characteristic data used on the respondent. The method used in this research is to use cross-sectional and then analyze the connection between variables with Chi-Square, the study was performed on 50 participants and the findings showed no connection between drug use compliance traits (P = 0.231).